Evidence on the Use of Non- Financial Reports based Information: Sources and Causes - D, Saadaby M.; H, Mohamed El-Amin T (Gezira Journal of Economic and Social Sciences; Vol 5 No 2 (2014), 2014)
A tendency to use non-financial reports based information is noticed in the Sudan. This paper aimed at investigating the sources of information other than financial reports used by users in the Sudan to avoid the failure and shortages of financial reports in satisfying their needs. It focuses mainly on studying the causes that encourage users to tap sources of information other than financial reports. The data for the study is collected through the tool of questionnaire from two groups of respondents (users and auditors). Descriptive statistics and Mann-Whitney U test are used to analyze the perceptions of the two groups. The most important findings arrived at by the paper are that: many sources of non-financial reports based information -including advices from banks, consulting firms, financial analysts, companies' websites and corporate staff are applied in the Sudan. The users may resort to use these sources of information because they may contain additional or explanatory or complementary information to some of the information in the financial reports, in addition to the ease of use, understanding and quick access to the information provided by these sources. Furthermore, it might be available in Timely fashion.